Sudden Onset Iron Overload Cardiomyopathy After Liver Transplantation - Alma Habib MD; Adnan Shaaban MD; Julie Thompson MD; Srinath Chinnakotla MD; Cindy M. Martin MD; Gregory M. Vercellotti MD (Journal of Investigative Medicine High Impact Case Reports, 2023)
Iron overload cardiomyopathy has been described in patients who develop acute heart failure after liver transplantation but few reports of this are available. We present a case of a patient with end-stage liver disease who underwent a deceased donor liver transplantation and developed acute onset systolic heart failure with reduced left ventricular ejection fraction. A cardiac magnetic resonance image demonstrated late gadolinium enhancement with diffuse enhancement globally and T1 mapping with severely decreased pre-contrast T1 values suggesting iron overload cardiomyopathy. The patient was treated with iron chelating therapy as well as heart failure guideline-directed medical therapy with subsequent improvement in cardiac function on follow-up magnetic resonance images. Despite our patient’s diagnosis of iron overload cardiomyopathy, her iron studies showed normal serum iron and ferritin levels and no evidence of hepatic iron deposition in the transplanted liver.